An iodine-containing probe as a tool for molecular detection in secondary ion mass spectrometry. Issue 54 (16th June 2022) - Kabatas Glowacki, Selda; Agüi-Gonzalez, Paola; Sograte-Idrissi, Shama; Jähne, Sebastian; Opazo, Felipe; Phan, Nhu T. N.; Rizzoli, Silvio O.
Abstract : We developed here an iodine-containing probe that can be used to identify the molecules of interest in secondary ion mass spectrometry (SIMS) by simple immunolabelling procedures. Abstract : We developed here an iodine-containing probe that can be used to identify the molecules of interest in secondary ion mass spectrometry (SIMS) by simple immunolabelling procedures. The immunolabelled iodine probe was readily combined with previously-developed SIMS probes carrying fluorine, to generate dual-channel SIMS data. This probe should provide a useful complement to the currently available SIMS probes, thus expanding the scope of this technology.